If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -6x = 12 Reorder the terms: -6x + 9y = 12 Solving -6x + 9y = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9y' to each side of the equation. -6x + 9y + -9y = 12 + -9y Combine like terms: 9y + -9y = 0 -6x + 0 = 12 + -9y -6x = 12 + -9y Divide each side by '-6'. x = -2 + 1.5y Simplifying x = -2 + 1.5y
| -6x+9y=12 | | 7n+31=94 | | 7n+31=94 | | 53=-7+2s | | f(x)=x^3+11x^2+40x+48 | | 8(2x-3)-5=16 | | 9m+6=3m | | -6x-4(3x-14)=182 | | 4=9(4)+b | | 3-7(3x-9)+2x-12=-19 | | 3x^2-12=-5x | | 3(x+8)-5=16 | | .5=m | | -6x-4(3x-14)=1823 | | 9x+484-132x=512x | | 3-2(3x-1)=-2x-4(x-1) | | 74+74= | | 36x^2-234x-432=0 | | 6(x+8)=54 | | 9x^2-30x-5=0 | | -5x-12=3(x-6) | | -21x+8-6x=-76 | | -21x+8-6x=-76 | | -4=5(3)+b | | 1=2(7.5) | | (2b^2)(a^5)(2b^4a)=4b^6a^6 | | 180=(n-2)180 | | 2x+4=28+x | | 13x=11+y | | 2x^2-25=-5x | | -2y+x=11 | | 3n^2-36n=105 |